Occupational risk factors and breast cancer in Beijing, China: a hospital-based case–control study. Issue 2 (17th February 2022) - Li, Aihua; Shen, Zhuang; Sun, Zhifeng; Yun, Shuiying; Tian, Xingkuan; Hu, Zaifang; Yu, Guixin; Hu, Li; Wang, Zihuan; Ye, Yan
Abstract : Introduction: Studies on the association between breast cancer and occupational hazards are limited, especially in China. This is the first study to explore the relationship between breast cancer and occupational hazards in Beijing, China. Design: A hospital-based case–control study. Setting: Eight local hospitals in Beijing, China. Participants: A total of 973 female participants, comprising 495 cases and 478 controls, were recruited in our study. We identified patients who underwent diagnosis for breast cancer at one of the eight local hospitals in Beijing between 1 January 2015 and 31 December 2019; controls were individuals randomly matched from the same hospital where the cases were confirmed. Main outcome and measure: Least absolute shrinkage and selection operator (LASSO) regression was used to estimate the occupational risk factors associated with breast cancer, including night shift work history and work posture. Results: In the case group, the breast cancer type was mainly invasive, which accounted for 85.66% of all the breast cancer patients. Five risk factors were included in the final LASSO model, including body mass index (BMI), marital status, menopause, night shift work history and work posture. Furthermore, these risk factors were considered for multivariate logistic regression, and the analyses suggested that the risk of breast cancer was significantly associated with higher BMI (≥28.0 kg/m 2, OR: 2.85, 95% CI: 1.29 to 6.30); married status: married (OR: 2.67, 95% CI: 1.28 to 5.56) or divorced (OR: 4.51, 95% CI: 1.84 to 11.07); menopause (OR: 6.89, 95% CI: 5.07 to 9.36); night shift work (OR: 1.53, 95% CI: 1.11 to 2.11); and maximum standing or walking, and minimal sitting (OR: 1.80, 95% CI: 1.19 to 2.73). Conclusion: Breast cancer is associated with occupational risk factors. Night shift work, especially in a standing posture, can increase the incidence of breast cancer in women in Beijing, China.